KNOWLEDGE, ATTITUDE, AND BEHAVIOR ABOUT ABORTION AMONG ADULT WOMEN AT PEUNAYONG DISTRICT, BANDA ACEH, INDONESIA - EKA RUSDIANTO GUNARDI; ERIK A RAHMAN; BIRAN AFFANDI; MUHAMMAD IKHSAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Every year approximately 13% (78,000) of maternal death caused by unsafe abortion. Indonesia Family Planning Association predicts 2.5 million abortions per year and 1.5 million of them committed by teenagers. Adolescent reproductive health problems are more alarming year by year. Sexual behavior tends to be permissive and bold with limited knowledge of reproductive health has increased the risk of abortion. This study is to assess the knowledge, attitudes, and behavior regarding abortion in young adults. Methods: This is a descriptive cross-sectional study. The subjects were young women aged 18–24 years old who were fulfilled by inclusion and exclusion criteria. The knowledge, attitudes, and behavior were assessed using questionnaire. The results were analyzed using statistical program. Results: The total subjects recruited in this study were 55 subjects. Twenty-eight (50.9%) of subjects has a good knowledge and 27 (49.1%) of subjects had a moderate knowledge. Twenty-nine (52.7%) subjects had moderate attitudes and 36.4% of subjects had good attitude. Thirty (54.5%) of subjects had a good behavior regarding abortion. Conclusion: Most of the subjects had good level of knowledge and moderate attitude toward abortion.